Strategic issues in the reform of the criminal procedure code towards an inclusive and effective criminal justice system - Yusuf, Arni (Journal of Law Science, 2025)
Law Number 8 of 1981 established the Criminal Procedure Code (KUHAP) as the foundation of Indonesia's criminal justice system. However, the Criminal Procedure Code faces significant challenges in maintaining relevance to contemporary legal and societal developments, particularly regarding victim recovery, functional differentiation among law enforcement institutions, and the protection of suspects’ and defendants’ procedural rights. This research aims to evaluate the Criminal Procedure Code's effectiveness in addressing these challenges and propose reforms to create a more inclusive and effective criminal justice system. Employing normative descriptive and juridical-analytical methodologies, the study examines relevant legal provisions and identifies practical solutions. The key findings highlight the Criminal Procedure Code’s inadequacies in facilitating restorative justice for victims, its lack of clear institutional coordination mechanisms, and barriers to procedural rights accessibility for suspects and defendants. The research contributes by advocating for revisions to the Criminal Procedure Code to incorporate restorative justice principles for victim recovery, strengthen coordination among law enforcement agencies, and enhance the accessibility of procedural rights for suspects and defendants. These reforms aim to enhance the efficiency of the legal system and deliver substantive justice for all stakeholders involved.